2019
DOI: 10.1089/ars.2017.7482
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of p22phox by Hypoxia Promotes Pulmonary Hypertension

Abstract: p22phox-dependent NADPH oxidases contribute to the pathophysiology of PH induced by hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The main isoforms of Nox in endothelial cells are Nox1, Nox2, Nox4, and Nox5 and are the major sources of endothelial cell-derived ROS ( Touyz et al, 2011 ; Wingler et al, 2011 ; Cat et al, 2013 ). It has been confirmed that AngII activates Nox and promotes the production of ROS ( Qiu et al, 2015 ; Liu et al, 2016 ; Zhang et al, 2019 ). It is believed to increase ROS production via the Nox families by increasing their protein expression as well as their catalytic activity ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The main isoforms of Nox in endothelial cells are Nox1, Nox2, Nox4, and Nox5 and are the major sources of endothelial cell-derived ROS ( Touyz et al, 2011 ; Wingler et al, 2011 ; Cat et al, 2013 ). It has been confirmed that AngII activates Nox and promotes the production of ROS ( Qiu et al, 2015 ; Liu et al, 2016 ; Zhang et al, 2019 ). It is believed to increase ROS production via the Nox families by increasing their protein expression as well as their catalytic activity ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
“…It has been confirmed that AngII activates Nox and promotes the production of ROS ( Qiu et al, 2015 ; Liu et al, 2016 ; Zhang et al, 2019 ). It is believed to increase ROS production via the Nox families by increasing their protein expression as well as their catalytic activity ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, as indicated in this study, chronic hypoxia results in pulmonary vascular remodeling and right ventricular hypertrophy. This has not only been associated with an increase in pulmonary vascular resistance and right ventricular pressure due to increased afterload in chronic hypoxic mice 21,22 , but has also been associated with a decreased ability of conductance vessels to store and deliver the entire stroke volume of the right ventricle and ultimately resulting in a loss of pulmonary flow during diastole 23 . PTT values (or CPTT - Cardiopulmonary Transit Times) have been previously studied in humans by using the first pass radionuclide cardiography technique 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative controls were included with each run. For evaluation of each lung, small α-smooth muscle actin positive vessels less than 30 µm were identified in three randomly selected regions of interest covering an area of 1 mm 2 each 22 .…”
Section: Methodsmentioning
confidence: 99%